The Potential of Immune Modulation in Therapeutic HIV-1 Vaccination - Nabila Seddiki; Florence Picard; Léa Dupaty; Yves Lévy; Véronique Godot (Vaccines, 2020)
We discuss here some of the key immunological elements that are at the crossroads and need to be combined to develop a potent therapeutic HIV-1 vaccine. Therapeutic vaccines have been commonly used to enhance and/or recall pre-existing HIV-1-specific cell-mediated immune responses aiming to suppress virus replication. The current success of immune checkpoint blockers in cancer therapy renders them very attractive to use in HIV-1 infected individuals with the objective to preserve the function of HIV-1-specific T cells from exhaustion and presumably target the persistent cellular reservoir. The major latest advances in our understanding of the mechanisms responsible for virus reactivation during therapy-suppressed individuals provide the scientific basis for future combinatorial therapeutic vaccine development.